2012
DOI: 10.1107/s1600536812022775
|View full text |Cite
|
Sign up to set email alerts
|

MnBa2(HPO4)2(H2PO4)2

Abstract: Key indicators: single-crystal X-ray study; T = 173 K; mean (Mn-O) = 0.003 Å; R factor = 0.025; wR factor = 0.075; data-to-parameter ratio = 13.1. ] groups. These chains are held together by BaO 9 coordination polyhedra, developing into a three-dimensional structure. The O-HÁ Á ÁO hydrogen bonds additionally stabilize the structural set-up. Due to the ionic radius of Mn 2+ being much smaller than those of Ca 2+ and Cd 2+ , this may imply that their adopted structure type has a great tolerance for incorporating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Unlike in the known mixed divalent cation phosphates MBa 2 (HPO 4 ) 2 (H 2 PO 4 ) 2 (M = Ca, Cd, Mn) (Ben Tahar et al, 1999;Taher et al, 2001;Sun et al, 2012), only one type of phosphate tetrahedron was observed in Cs 3 (H 1.5 PO 4 ) 2 Á2H 2 O.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Unlike in the known mixed divalent cation phosphates MBa 2 (HPO 4 ) 2 (H 2 PO 4 ) 2 (M = Ca, Cd, Mn) (Ben Tahar et al, 1999;Taher et al, 2001;Sun et al, 2012), only one type of phosphate tetrahedron was observed in Cs 3 (H 1.5 PO 4 ) 2 Á2H 2 O.…”
Section: Resultsmentioning
confidence: 73%
“…Three bands ($2790, 2350 and 1745 cm À1 ) are observed in the O-H stretching and bending region of the IR spectrum, confirming the presence of strong hydrogen bonds. These spectral characteristics have been observed in a variety of strong hydrogen-bonded solids having OÁ Á ÁO distances varying from 2.4 to 2.6 Å (Taher et al, 2001;Sun et al, 2012;Marchon & Novak, 1983;Baran et al, 1989). The band with a maximum lying at 2350 cm À1 and a shoulder around 2200 cm À1 may be related to the presence of two different types of hydrogen bonds with different lengths.…”
Section: Figurementioning
confidence: 85%